Pantallas de visualización de datos y su influencia en la fatiga visual del personal administrativo del Cuerpo de Bomberos, Los Ríos – Babahoyo, noviembre 2023 – abril 2024. - Moreira Ortiz, Alisson Anahi (2024)
The research project focuses on the influence of data display screens on the visual fatigue of the administrative staff of the Fire Department of the city of Babahoyo. The problem raised highlights the growing use of screens in work environments and their possible negative effects on visual health. The objective is to determine the influence of data display screens on the visual fatigue of the administrative staff of the Fire Department, Los Ríos – Babahoyo, November 2023 - April 2024. The methodology of this research according to the level of study is descriptive, applying the use of tests such as optometric tests and the taking of clinical histories to evaluate visual acuity before and after the work day. The results showed that the influence of data display screens on the results of visual acuity with correction, the appearance of accommodative dysfunctions can also be associated with the use of these devices, in the same way that ocular symptoms are effects that occur after the use of PVD. It was concluded that this study seeks to provide relevant information on how data display screens influence the visual fatigue of administrative personnel of the Fire Department, with the purpose of improving working conditions and preventing possible long-term visual problems.